1986
DOI: 10.1128/jvi.59.2.401-410.1986
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and processing of bovine herpesvirus 1 glycoproteins

Abstract: Four unique glycoproteins or glycoprotein complexes were recognized by a panel of monoclonal antibodies to bovine herpesvirus 1 (BHV-1), i.e., GVP 6/lla/16 (130,000-molecular-weight glycoprotein [130K glycoprotein]/74K/55K), GVP 7 (108K), GVP 3/9 (180K/91K), and GVP llb (71K). The absence of any antigenic or structural relationship between GVP lla and GVP llb, which were previously identified as one glycoprotein, GVP 11, demonstrated that these two GVP 11 species are unique glycoproteins. GVP 3 and GVP 9 showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
41
0

Year Published

1988
1988
2008
2008

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 107 publications
(47 citation statements)
references
References 51 publications
6
41
0
Order By: Relevance
“…7b) to monitor the reactions. According to the enzymes used, the electrophoretic mobilities of virion-associated gD increased as expected (41), and no differences were detected in comparison to the reaction products of immunoprecipitated virion gD (Fig. 7b and c), indicating the presence of sufficient enzymatic activity for complete deglycosylation within the respective probes.…”
Section: Transcription Of the Brsv G Ori And Brsv G Syn Orfs In Recomsupporting
confidence: 70%
“…7b) to monitor the reactions. According to the enzymes used, the electrophoretic mobilities of virion-associated gD increased as expected (41), and no differences were detected in comparison to the reaction products of immunoprecipitated virion gD (Fig. 7b and c), indicating the presence of sufficient enzymatic activity for complete deglycosylation within the respective probes.…”
Section: Transcription Of the Brsv G Ori And Brsv G Syn Orfs In Recomsupporting
confidence: 70%
“…5, panel gIV), indicating that it entered the normal secretory pathway through the Golgi apparatus, where N-linked oligosaccharides on gIV were modified from the high-mannose to the complex type prior to transport of gIV to the cell surface. These results suggest that the gIV produced by recombinant VV (STgIV) is processed in a way similar to that in which gIV is produced during BHV-1 infection (23).…”
Section: Methodsmentioning
confidence: 90%
“…Earlier studies have shown the presence of both N-linked and 0-linked oligosaccharides in gIV (23). In BHV-1-infected cells, N-linked oligosaccharides are processed from high-mannose oligosaccharides present on precursor gIV to complex oligosaccharides of mature gIV, which is transported to the surface of an infected cell and also incorporated into the virion envelope (14,20).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Glycoprotein gB, gC and gD have been identified as the major immunogens. These are expressed at high levels on the virion envelope and on the plasma membrane of virus infected cells (2). Their biological properties have been reviewed (3).…”
Section: Introductionmentioning
confidence: 99%